Association of genetic variants with level of asthma control in the Arab population - Almomani, Basima A (J Asthma Allergy, 2019)
BACKGROUND: Rates of asthma in Jordan have been doubled in the past decade, but this increased prevalence was not met with improved asthma control protocols. The aim of the present study was to assess whether there was any significant association between the level of asthma control and certain single-nucleotide polymorphisms (SNPs) in five genes: (ADRB2; rs1042713 and rs1042714), (CRHR1; rs1876828, rs242939, and rs242941), (STIP1; rs2236647), (ADH5, rs1154400), and (ARG1; rs2781659). These SNPs were selected based on their involvement in enzymes and receptors that are related to asthma pathways and subsequent response to medication and based on a high degree of linkage disequilibrium. PATIENTS AND METHODS: A cross-sectional genetic association study was conducted from June 2016 to June 2017 in the two major hospitals in Jordan. The present study involved sampling from adult asthmatic patients of Arab descent who were selected from two phenotypic groups, ie, controlled and uncontrolled asthma. The blood samples and medical data were collected from the participants. DNA samples were extracted, quantified, and genotyped according to standard operating procedure. Allelic and haplotypic analyses were performed using the Haploview(®). RESULTS: A total of 245 Arab asthmatic patients were enrolled in this study. Genotyping analysis revealed that the two SNPs (rs1042713 and rs1042714) in ADRB2 gene, along with their related haplotypes, were nominally significantly associated with asthma control in the Jordanian population. The A-allele of rs1042713 and the C-allele of rs1042714 were more common in the uncontrolled asthma group than in the controlled asthma group (P=0.048 and P=0.017, respectively). CONCLUSION: This was the first study that identified the nominal significant association between the level of asthma control and genetic variants in ADRB2 gene in Arab population. Further studies in other Arab region with larger sample size are recommended to confirm the relationship.